The Relation Between Vision Distance, Body Posture, And Long Use of Computer with Computer Vision Syndrome in Faculty of Medicine Universitas Sumatera Utara - Fadillah Tarigan, Muhammad; Amelia, Rina (Jurnal KESANS : Kesehatan dan Sains, 2022)
Background: The COVID-19 pandemic affects all activities of human life, including education. Educational activities that are usually carried out face-to-face in class have now been stopped to avoid the expansion of the spread of COVID-19. The cessation of face-to-face learning activities is shifted to online-based learning (distance) by utilizing technology that is connected to the internet. This distance learning system applies to all levels of education. Learning with an online system using a computer all day makes various complaints experienced by students such as computer vision syndrome. The most common eye complaints condition is computer vision syndrome, some eye and vision problems that originate from prolonged use of computers, tablet computers, electronic readers, and mobile phones. Computer Vision Syndrome is a collection of symptoms in the eyes and neck caused by excessive use of computers/monitors. Symptoms vary but mostly involve eye strain, headache, blurred vision, dry eyes, irritation, slowed focusing of the eyes, pain in the neck, back, and sensitivity to light. Objective: The purpose of this study was to analyze the relationship between visibility, body posture, and duration of computer use with Computer Vision Syndrome (CVS) in USU Medical Faculty students Methods: This type of research is analytic with a cross-sectional study approach. The sample of this study amounted to 100 students who were randomly selected using stratified random sampling. The data used is primary data from questionnaires filled out online through the Line, WhatsApp, and Instagram applications. Data analysis using SPSS with chi-square statistical test (p <0.05). Results: The results showed that the most visibility was < 50 c, frequent bad posture, and duration of use was > 4 hours. Conclusion: The results showed that there was a relationship between visibility, body posture, and duration of using a computer with CVS for USU Medical Faculty students.